Demodicose bovina no estado da Paraíba - Faccini, João Luiz H.; Santos, Ana Clara G.; Bechara, Gervásio H. [UNESP] (FapUNIFESP (SciELO), 2004)
Cases of bovine demodicosis caused by Demodex bovis were reported in a Sindhi herd from December 1989 to January 1992. Both localized and generalized forms were diagnosed. This is the first report of the generalized form in Brazil. In the first two years, demodicosis was diagnosed only in cattle < 2 years old, whereas animals of all ages were positive in the last two years. Prevalence varied from 20.4% (11/54) to 53.1% (26/49) and 13.2% (12/91) to 14.8% (9/61) for cattle < 2 years old and > 2 years old, respectively. Clinical signs varied from a few small nodules to a thickened skin with soft large nodules in the localized and generalized forms, respectively. Main microscopic features of the nodules in the generalized form consisted of acanthosis with hyperqueratosis, chronic sebaceous adenitis, subcutaneous muscular necrosis, focal cellular degeneration of the epidermis basal layer and presence of large number of mites inside the lumen of dilated hair follicles. In addition, a chronic perifoliculitis was observed, characterized by lymphoplasmocytic infiltrate which also contained macrophages and neutrophils. It is suggested that poor nutrition and stress due to prolonged drought probably contributed to the increase of susceptibility of the herd to mite infestation.
Bovine demodicosis in the state of Paraíba, northeastern Brazil
Keywords: Brazil; Cattle; Demodex bovis; Demodicosis; Pathology; acanthosis; cattle disease; cell infiltration; clinical feature; cow; Demodex; demodicidosis; diagnostic test; hair follicle; mite; nonhuman; prevalence; Acari; Animalia; Bos taurus; Bovinae